Outer membrane vesicles-transmitted virulence genes mediate the emergence of new antimicrobial-resistant hypervirulent Klebsiella pneumoniae - Yuneng Hua (Emerging Microbes and Infections, 2022)
Hypervirulent Klebsiella pneumoniae (hvKp) is a notorious clinical pathogen that is more likely to cause severe primary and metastatic abscesses. The dissemination of antimicrobial-resistant hvKp isolates has been reported worldwide, posing a great challenge and severe clinical threat. However, the mechanisms of antimicrobial-resistant hvKp isolates prevalent worldwide are not well precise. Outer membrane vesicles (OMVs) secreted from gram-negative bacteria are an important vehicle for delivering effector molecules inter- and intra-species. To explore whether OMVs as the vector of virulence genes horizontal transfer among Klebsiella pneumoniae and to explain the potential mechanism for the development of antimicrobial-resistant hvKp isolates, we isolated OMVs from hvKp and classical Klebsiella pneumoniae (cKp) by sequential differential centrifugation, respectively. Then, the characteristics and contents of hvKp-OMVs and cKp-OMVs were analyzed. These hvKp-OMVs contain virulence genes, which could be transferred from hvKp horizontally to extended-spectrum beta lactamase (ESBL)-producing cKp, leading to the production of antimicrobial-resistant hypervirulent transformants. Further experiments confirmed the transformants exhibited antimicrobial resistance and hypervirulent phenotypes in vitro and in vivo. In short, this work demonstrated that hvKp-OMVs facilitated virulence genes transfer, allowing an increase in the virulence level of ESBL-producing cKp and providing a new mechanism for the emergence of antimicrobial-resistant hvKp isolates.